(untitled) (Psicologia USP, 2009)
This article has as an objective to reflect concerning the concept of psychic transmission among generations, specifically of one modality - the transgenerational psychic transmission - and its influence on the creation of the individual subjectivities and of the family links, being emphasized mainly the link of mother-daughter as generator of symptoms in the child and familiar conflicts, through a clinical report of a psychoanalytic linkage psychotherapy, according to the references of Eiguer (2006) and Berenstein and Puget (1997, 2005). The presentation of the clinical case allows discussing the relationship between the transgenerational psychic transmission and the establishment of the primary maternal preoccupation as well as the results obtained along the whole psychotherapeutic process. The purpose of this family therapeutic space is to offer transformations join to the generational legacy promoting the appearance of a new subjectivity generating of life.